2015
DOI: 10.1002/esp.3834
|View full text |Cite
|
Sign up to set email alerts
|

Confirming geomorphological interpretations based on portable OSL reader data

Abstract: Portable optically stimulated luminescence (OSL) readers are increasingly being used in geomorphological and archaeological investigations, but information regarding data reproducibility and the reliability of interpretations based on portable OSL reader data has not yet been presented to the wider geomorphological community. This Letter addresses these two issues by returning to Grabben Gullen Creek in the southeastern Australian Tablelands where we remeasure a sediment profile that was first measured by othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 27 publications
5
43
0
Order By: Relevance
“…The key conclusion from their work is that the upstream soils developed over metasedimentary rocks have low total photon counts and are not likely sources for post‐colonization deposits with higher total photon counts as sediment transport downstream should either decrease or keep the total photon counts constant with transport distance. The findings of Muñoz‐Salinas et al () were later shown to be reproducible by data given by Portenga and Bishop (), who agreed with interpretations by Muñoz‐Salinas et al (). Portenga et al () would later expand the Muñoz‐Salinas et al () approach to various other regional sites allowing for a wider‐scale interpretation of river basin change.…”
Section: Luminescence As a Provenance Toolsupporting
confidence: 74%
“…The key conclusion from their work is that the upstream soils developed over metasedimentary rocks have low total photon counts and are not likely sources for post‐colonization deposits with higher total photon counts as sediment transport downstream should either decrease or keep the total photon counts constant with transport distance. The findings of Muñoz‐Salinas et al () were later shown to be reproducible by data given by Portenga and Bishop (), who agreed with interpretations by Muñoz‐Salinas et al (). Portenga et al () would later expand the Muñoz‐Salinas et al () approach to various other regional sites allowing for a wider‐scale interpretation of river basin change.…”
Section: Luminescence As a Provenance Toolsupporting
confidence: 74%
“…The depth trends of bulk OSL data through PSA and SM sediments at Birchams Creek resemble SM and SM‐PSA profiles found elsewhere in the Tablelands [ Muñoz‐Salinas et al ., ; Portenga et al ., ] (Figure a); we note, however, that SM sediments at ~90 cm deep at site SM‐1 show a substantial decrease in bulk OSL that is not observed in SM sediment profiles elsewhere in the Tablelands [ Portenga and Bishop , ]. Without further sampling or deriving ages throughout the SM‐1 profile, we can only speculate that this decrease may represent a former valley bottom surface.…”
Section: Discussionmentioning
confidence: 99%
“…PSA deposits throughout the Tablelands were transported and deposited by floods; the higher bulk OSL measurements at the base of PSA compared to those in the uppermost SM sediments indicate that PSA was minimally bleached before deposition and that peak bulk OSL measurements reflect bulk OSL from the PSA source material [Muñoz-Salinas et al, 2014;Portenga and Bishop, 2016;Portenga et al, 2016a]. Thus, to be considered as a reasonable source for PSA, potential sources of PSA (e.g., SM-1 and VF-1) must contain sediment with bulk OSL values greater than or equal to the bulk OSL maxima of PSA deposits (e.g., PSA-1 and PSA-2; Figure 5a).…”
Section: Identifying Psa Source Locations and Depthsmentioning
confidence: 99%
“…Creek, Australia (Portenga & Bishop 2015), as well as for sediments trapped in reservoirs (e.g. Bishop et al 2010 in the Baldernock Mill dam, Scotland).…”
Section: And In Grabben Gullenmentioning
confidence: 95%
“…Several studies have employed a PPSL reader in fluvial settings to study how luminescence signals in alluvium and debrisflows change within river basins around the world (e.g. Muñoz-Salinas et al 2011a, b, 2013, 2016 and in Grabben Gullen Creek, Australia (Portenga & Bishop 2015), as well as for sediments trapped in reservoirs (e.g. Bishop et al 2010 in the Baldernock Mill dam, Scotland).…”
mentioning
confidence: 99%